Changes in Media Consumption Patterns and their Implications for People's Cultural Identity - Sutrisno, Sutrisno (PT. LITERASI SAINS NUSANTARA, 2023)
In the era of globalisation and the rapid development of information technology, mass media has become an integral part of people's lives. Media is not only a source of information, but also plays an important role in shaping a society's views, values and cultural identity. This research aims to analyse changes in media consumption patterns and their implications for people's cultural identity. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and texts from various sources. The results show that changes in media consumption patterns in the era of globalisation have a significant impact on people's cultural identity. Easier access to different types of media content from around the world has opened up opportunities for cross-cultural interaction and information dissemination. However, this also brings challenges in maintaining a balance between the preservation of local cultural identity and the influence of global culture. People's cultural identity is formed through a complex dynamic between traditions, values and the influence of modern media.